PERSPEKTIF MASLAHAH MURSALAH TENTANG IMPLEMENTASI AKAD QARDH DALAM PEMBIAYAAN USAHA MIKRO DI BANK WAKAF MIKRO AL-ANSHOR PEDULI KOTA AMBON - Holle, Muhammad H; Wanci, Sardin (Institut Agama Islam Negeri (IAIN) Ternate, 2021)
The purpose of this study was to describe the implementation of qardh contract financing at Al-Anshor Peduli Micro Waqf Bank Ambon, and to find out Maslahah Mursalah's Perspective on Qardh Contract Implementation in Micro Business Financing at Al-Anshor Peduli Micro Waqf Bank Ambon City. This research was conducted using qualitative descriptive techniques and field studies (library research). The results of the study: 1. qardh financing is carried out by socializing to micro business actors or community members who want to start a business. 2. Utilization of the qardh contract in accordance with the principle of maslahah mursalah, according to the perspective of maslahah mursalah. Implementation of credit financing qardh contracts to provide benefits for micro business actors who have difficulty working capital and people who want to start a business but lack funds.